Analysis and Optimization of Delamination Factor during Drilling of E-Glass/Epoxy Composite by Taguchi Method - D.S.Balaji,; K.Umanath,; S.Prabhakaran,; P.Ramesh,; V.Kurinji, (International Journal of Psychosocial Rehabilitation, 2020)
Composites are widely being used to replace the conventional metals in many industrial applications including Aircraft, Aerospace and defence due to its high strength to weight ratio. Delamination is the common problem that is faced during the drilling of composites. This paper presents the effect of Feed rate, Cutting speed and Drill Bit Material on delamination behaviour on composite material by conducting drilling experiments using L9 orthogonal array. The output parameters considered here is Delamination factor the corresponding Material Removal rate (MRR), Thrust Force, Torque and Power are calculated. The effects of these parameters on Delamination will be studied based on the experimental results , also useful recommendations will be given in order to select the suitable process parameters in Drilling of a GFRP composite using Taguchi Technique